Late Rebound of Infantile Hemangioma after Cessation of Oral Propranolol. Issue 5 (10th September 2013) - Shehata, Nancy; Powell, Julie; Dubois, Josée; Hatami, Afshin; Rousseau, Elizabeth; Ondrejchak, Sandra; McCuaig, Catherine
Abstract Propranolol has become the first line of treatment for infantile hemangiomas (IHs), with a high response rate, but rebound growth after cessation of propranolol has been reported, primarily in the first year of life. We sought to determine the frequency and associated factors leading to late regrowth after successful treatment at an age when the proliferative phase has usually ceased. We retrospectively reviewed the clinical charts, serial photographs, and radiologic images of children with rebound IH occurring after the age of 15 months after a successful course of oral propranolol averaging 2.6 mg/kg/day (range 2–3 mg/kg/day). Thirteen (10 female, 3 male) of 212 patients (6%) treated with oral propranolol since 2008 were evaluated. The mean age at the start of treatment was 5.3 months (range 1.8–13 months), and an average of 10.3 months (range 4.5–16 months) of treatment was given. It took an average of 5.3 months (range 1–13.8 months) for a significant rebound to appear. Late rebound after successful propranolol indicates a prolonged proliferation phase of IH even after 15 months of age. This is compared with previous reports of rebound, which occurred primarily in infants younger than 1 year old. Late proliferation can occur in localized, small, mixed, and deep IH, even after several months of a positive response to propranolol. A second course of propranolol readily controlled the recurrence.